Exploring transgenerational entrepreneurship : the role of resources and capabilities (2014)
Families are engines of economic activity around the world. In many cases their economic impac lasts for centuries and generations. This phenomenon is referred to as transgenerational entrepreneurship (TE) and is defined as the processes, resources and capabilities used by an enterprising family to create financial and socio-emotional value across generations (cf., Habbershon et al., 2010). Te shifts the level of analysis to the family. It examines how the longevity of family enterprises extends beyond the life cycle of any individual operating entity (Zellweger et al., 2013). As Penrose highlights in her seminal work,, Theory of the Growht of the Firm (1959), the nature of the firm’s resources. The aim of this book is to understand how successful enterprising families in different contexts build and exploit resources and capabilities to create entrepreneurial ventures across generations. We focus on a specific theme within TE – the role of intangible resources and capabilities.